MELIORATING EFFECT OF L-ASCORBIC ACID ON PROFENOFOS INDUCED ALTERATIONS IN THE PROTEIN CONTENTS OF THE FRESHWATER BIVALVE, LAMELLIDENS MARGINALIS (LAMARCK) - WAYKAR BHALCHANDRA; ULATE PRAKASH (The Bioscan, 2011)
The freshwater bivalve Lamellidens marginalis were exposed to chronic dose of Profenofos, 0.6191 ppm (LC50/ 10) alone and in combination with 50mg/L L-ascorbic acid for 21 days. Percent protein contents in the mantle, foot, gill, digestive glands and whole body of control bivalve, Lamellidens marginalis were 41.76±1.50, 60.49±1.30, 51.52±0.62, 47.52±0.53 and 57.14± 1.88 respectively. Percent protein contents in the mantle, foot, gill, digestive glands and whole body of bivalve, Lamellidens marginalis on Profenofos intoxication were 21.98±2.54 (p<0.001),41.48±1.87 (p<0.01), 22.78±2.04 (p<0.01),16.68±1.03 (p<0.05) and 30.77± 2.09 (p<0.01) respectively. Percent protein contents in the mantle, foot, gill, digestive glands and whole body of bivalve, Lamellidens marginalis on exposure to Profenofos with 50mg/L L-ascorbic acid were 30.77±2.04 (p<0.001), 45.24±1.45 (p<0.01), 29.96±1.25 (p<0.001), 32.23±1.52 (p<0.05) and 35.56± 1.94 (p<0.01) respectively. Protein contents in the mantle, foot, gill, digestive glands and whole body of profenophos and Profenophos with 50mg/L L-ascorbic acid exposed bivalve, Lamellidens marginalis showed remarkable decrease in protein content as compared to control. The higher depletion of protein was observed in digestive glands as compared to other tissues. Exposure to pesticide Profenofos in combination with 50 mg/L of L-ascorbic acid showed considerable reduction in the depletion of protein levels. The pre-exposed bivalves for 21 days exposure to chronic dose of Profenofos showed recovery in normal water and the protein contents were increased to 28.16±0.5 (p<0.001), in mantle, 48.56±0.23 (p<0.01), in foot, 30.27±0.45 (p<0.001), in gill, 24.77±0.24 (p<0.001), in digestive glands and 43.96±2.05 (p<0.001), in whole body while percent protein contents in presence of 50mg/L of L-ascorbic acid were increased to 34.63±1.82 (p<0.01), in mantle, 57.15±2.24 (p<0.01), in foot, 39.42±0.46(p<0.01), in gill, 30.16±0.79 (p<0.05), in digestive glands and 52.04±0.45 (p<0.001), in whole body. Fast recovery of percent protein contents was observed in presence of L-ascorbic acid than the recovery in the normal freshwater. This study indicates the protective and curative property of the L- ascorbic acid against the Profenofos induced damage.